Genotypic characterization of Toxoplasma gondii in sheep from Brazilian slaughterhouses: New atypical genotypes and the clonal type II strain identified - da Silva, Rodrigo Costa [UNESP]; Langoni, Hélio [UNESP]; Su, Chunlei; da Silva, Aristeu Vieira (Elsevier B.V., 2011)
Toxoplasma gondii strains are genetically diverse in South America. To date, hundreds of T. gondii isolates from different animal hosts were genotyped in Brazil, most of them are different from those identified around the world. This study aimed to determine T. gondii infection rate in sheep from Brazilian slaughterhouses, as well as the genotype of these isolates. T. gondii antibodies were detected in 66/602 (10.96%) serum samples through modified agglutination test (MAT) and indirect fluorescent antibody test (IFAT). MAT-HS and IFAT-IgG presented high concordance (0.95) and strong correlation (r = 0.79). T. gondii DNA was detected in tissue samples of 33% (22/66) serum positive sheep by PCR of the 529 bp repetitive element. In the bioassay in mice, T. gondii were detected in mice brain or muscle tissues in 30% (20/66) of serum positive sheep. Positive samples were typed through Restriction Fragment Length Polymorphism (RFLP-PCR) using 11 markers: SAG 1, SAG2 (5'-3'SAG2 and alt.SAG2), SAG3, BTUB, GRA6, 1358, c22-8, c29-6. PK1. Apico and CS3. of 22 samples, 13 were positive and 9 genotypes were identified. Four of these 9 genotypes are unique. Nine samples had negative results in RFLP-PCR typing, which may be due to low DNA concentration. Six isolates were virulent killing mice between 12 and 25 days postinfection. Two non-virulent isolates belonged to clonal type II genotype, which were not observed in Brazil previously. These findings confirm the high diversity and high frequency of virulent genotypes among Brazilian animals. This study also proved the presence of type II T. gondii in Brazil. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; High divergence genotypes; Sheep; Clonal type II; RFLP-PCR typing; Slaughterhouse